1997
DOI: 10.1093/emboj/16.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Chk1 is a wee1 kinase in the G2 DNA damage checkpoint inhibiting cdc2 by Y15 phosphorylation

Abstract: The G2 DNA damage checkpoint ensures maintenance of cell viability by delaying progression into mitosis in cells which have suffered genomic damage. It is controlled by a number of proteins which are hypothesized to transduce signals through cell cycle regulators to delay activation of p34cdc2. Studies in mammalian cells have correlated induction of inhibitory tyrosine 15 (Y15) phosphorylation on p34cdc2 with the response to DNA damage. However, genetic studies in fission yeast have suggested that the major Y1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
331
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 372 publications
(348 citation statements)
references
References 41 publications
(60 reference statements)
11
331
0
2
Order By: Relevance
“…In S. pombe several mutants have been described that are unable to arrest the cell cycle in response to DNA damage at the G2 checkpoint (Weinert and Hartwell, 1990;AlKhodairy et al, 1994;Ford et al, 1994). One of these genes, chk1, encodes a protein kinase that appears to function downstream of all other checkpoint genes to elicit a cell cycle arrest via cdc25 and wee1 to maintain tyrosine phosphorylation of p34 cdc2 (O'Connell et al, 1997;Rhind et al, 1997;Furnari et al, 1997;Sanchez et al, 1997). Irradiation of cells leads to phosphorylation of chk1 itself, and this response requires all of the upstream checkpoint components, including rad3 (Walworth and Bernards, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In S. pombe several mutants have been described that are unable to arrest the cell cycle in response to DNA damage at the G2 checkpoint (Weinert and Hartwell, 1990;AlKhodairy et al, 1994;Ford et al, 1994). One of these genes, chk1, encodes a protein kinase that appears to function downstream of all other checkpoint genes to elicit a cell cycle arrest via cdc25 and wee1 to maintain tyrosine phosphorylation of p34 cdc2 (O'Connell et al, 1997;Rhind et al, 1997;Furnari et al, 1997;Sanchez et al, 1997). Irradiation of cells leads to phosphorylation of chk1 itself, and this response requires all of the upstream checkpoint components, including rad3 (Walworth and Bernards, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism(s) for G2 checkpoint activation in response to DNA damage remains unclear but recent data with S. pombe support a model where chk1 protein kinase maintains p34 cdc2 in its tyrosine phosphorylated, inactive state for the duration of the checkpoint arrest (O'Connell et al, 1997;Rhind et al, 1997). Overexpression of chk1 in wild type S. pombe led to cellular elongation and a failure to enter mitosis (Al-Khodairy et al, 1994;Ford et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When DNA is damaged, the cell cycle can be arrested at the G1 phase or the G2 phase of the cell cycle. Recently, details of the G2 DNA damage checkpoint (G2DDC) pathway that impinges on the cell cycle have been elucidated (Nurse, 1997;Weinert, 1997). It is now being suggested that the G2DDC pathway perturbs the cell cycle via Cdc25 (Furnari et al, 1996;Rhind et al, 1997).…”
Section: Coupling Of the Pd Cycles Involving Cdc25 Wee1 And Mpfmentioning
confidence: 99%
“…When there is DNA damage, there is a sensing mechanism (called a checkpoint pathway) that detects this damage and transduces the information to the cell cycle machinery. The G1 DNA damage checkpoint pathway has been studied extensively (Carr, 1996) and, recently, more details about the G2 DNA damage checkpoint (G2DDC) pathway are being elucidated (Nurse, 1997;Weinert, 1997). A second objective of this paper is to study how the G2DDC pathway impinges on the cell cycle and to propose a resolution of the issue on the identity of the cell cycle protein targeted by the G2DDC pathway (Osmani and Ye, 1997).…”
Section: Introductionmentioning
confidence: 99%